RNAseq Reveals Complex Response of Campylobacter jejuni to Ovine Bile and In vivo Gallbladder Environment - Kreuder, Amanda J.; Schleining, Jennifer A.; Yaeger, Michael; Zhang, Qijing; Plummer, Paul J. (Frontiers in Microbiology, 2017)
Colonization of the gallbladder by enteric pathogens such as Salmonella typhi, Listeria monocytogenes, and Campylobacter jejuni is thought to play a key role in transmission and persistence of these important zoonotic agents; however, little is known about the molecular mechanisms that allow for bacterial survival within this harsh environment. Recently, a highly virulent C. jejuni sheep abortion (SA) clone represented by the clinical isolate IA3902 has emerged as the dominant cause for sheep abortion in the United States. Previous studies have indicated that the C. jejuni clone SA can frequently be isolated from the gallbladders of otherwise healthy sheep, suggesting that the gallbladder may serve as an important reservoir for infection. To begin to understand the molecular mechanisms associated with survival in the host gallbladder, C. jejuni IA3902 was exposed for up to 24 hours to both the natural ovine host in vivo gallbladder environment, as well as ovine bile in vitro. Following exposure, total RNA was isolated from the bile and high throughput deep sequencing of strand specific rRNA-depleted total RNA was used to characterize the transcriptome of IA3902 under these conditions. Our results demonstrated for the first time the complete transcriptome of C. jejuni IA3902 during exposure to an important host environment, the sheep gallbladder. Exposure to the host environment as compared to in vitro bile alone provided a more robust picture of the complexity of gene regulation required for survival in the host gallbladder. A subset of genes including a large number of protein coding genes as well as seven previously identified non-coding RNAs were confirmed to be differentially expressed within our data, suggesting that they may play a key role in adaptation upon exposure to these conditions. This research provides valuable insights into the molecular mechanisms that may be utilized by C. jejuni IA3902 to colonize and survive within the inhospitable gallbladder environment.